The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10552-006-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations among maternal soy intake, isoflavone levels in urine and blood samples, and maternal and umbilical hormone concentrations (Japan)

Abstract: AbsractObjectives In utero exposure to high levels of endogenous estrogens has been hypothesized to increase breast cancer risk in later life. A high intake of soy has been suggested to protect against breast cancer. We examined the hypothesis that maternal soy intake may be inversely associated with pregnancy hormone levels. Methods The concentrations of hormones (estradiol, estriol, and testosterone) and isoflavones (genistein, deidzein, and equol) were measured in the maternal urine and serum, and umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
(30 reference statements)
2
28
0
1
Order By: Relevance
“…Plasma concentrations of 50e800 ng/ml have been found for GEN in adults who consume modest amounts of soy foods Setchell and Cole, 2003). Thus, fetus can be actively exposed to GEN by mothers who consume soy products during pregnancy since a high correlation has been observed for isoflavone serum levels between maternal and umbilical cord blood samples, indicating that GEN can be easily transferred to the fetus by placenta (Nagata et al, 2006). This isoflavone is often categorized as a phytoestrogen because of its ability to bind to estrogen receptors (ERs) but display weak estrogenic activity when compared to the estrogen (Vitale et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of 50e800 ng/ml have been found for GEN in adults who consume modest amounts of soy foods Setchell and Cole, 2003). Thus, fetus can be actively exposed to GEN by mothers who consume soy products during pregnancy since a high correlation has been observed for isoflavone serum levels between maternal and umbilical cord blood samples, indicating that GEN can be easily transferred to the fetus by placenta (Nagata et al, 2006). This isoflavone is often categorized as a phytoestrogen because of its ability to bind to estrogen receptors (ERs) but display weak estrogenic activity when compared to the estrogen (Vitale et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple maternal factors including age, BMI, psychological status, dietary and nutriment intake, and medication use are all associated with hormone levels during gestation [53], [68], [69], [70]. Several epidemiological studies that focused on the effects of endocrine disrupting substances have shown that toxicants exposure such as polybromodiphenyl ethers and phthalates may affect hormone levels of pregnant women and neonates [71], [72], [73].…”
Section: Discussionmentioning
confidence: 99%
“…The detection rates of phytoestrogens, genistein, daidzein and equol in the umbilical cord of the newborns were 100%, 80% and 35%, respectively [46]. Within this perspective, Nagata et al [47] also showed high correlations to isoflavone levels between samples of maternal and umbilical cord blood of 194 accompanied women during pregnancy [47].…”
Section: Soy and Metabolic Programmingmentioning
confidence: 97%
“…In the context of this discussion, it is important to emphasize the ability of placental transfer of phytoestrogens from mother to fetus [46,47]. In this sense, 51 Japanese mothers were accompanied by the time of cesarean section, where we collected serum sample of the mother and the umbilical cord.…”
Section: Soy and Metabolic Programmingmentioning
confidence: 99%